2019
DOI: 10.3390/resources8020088
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Threats of Implementing Drain Water Heat Recovery Units in Poland

Abstract: In recent years an increase of interest in usage of renewable energy sources as a substitution of fossil fuels is being noticeable. However, the waste heat potential, which can be used as an additional source of energy for heating water in buildings, is being omitted. The sources of this heat can be grey water discharged from such sanitary facilities as showers or washing machines. In response to this issue, we took on the task to define and analyze key factors affecting the development of DWHR (Drain Water He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…However, the research finding has revealed that the independent variable reduction in water consumption has a positive and significant impact on ROA. This findings similar to Al-Zubari et al 2018; Kordana et al (2019) as revealed that reduction water consumption has a positive and significant impact on ROA and set opposes of the result of Bassey et al (2013); Neeveditah et al (2017). Therefore, this hypothesis (H3) is Accepted.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…However, the research finding has revealed that the independent variable reduction in water consumption has a positive and significant impact on ROA. This findings similar to Al-Zubari et al 2018; Kordana et al (2019) as revealed that reduction water consumption has a positive and significant impact on ROA and set opposes of the result of Bassey et al (2013); Neeveditah et al (2017). Therefore, this hypothesis (H3) is Accepted.…”
Section: Resultssupporting
confidence: 81%
“…However, Bassey et al (2013) directed the research and found that Water recycling, on the contrary, had a negative influence on EBITA/ROA and Positive relationship with ROE indicating loose in revenue (Bassey et al, 2013). Another study revealed, the obtained result shows that most favourable financial effects can be achieved by reducing water consumption (Kordana et al, 2019). Further study reveals that there is an insignificant relationship between water management practices and financial performance (Neeveditah et al, 2017).…”
Section: Resultsmentioning
confidence: 82%
“…SWOT and PESTLE analysis is concluded in these methods. Advantages and disadvantages of DR aggregators were discussed in [9] from political, economic, social and technological (PEST) point of views. Based on this analysis, a strengths, weaknesses, opportunities, and threats (SWOT) analysis for a typical DR aggregator was presented.…”
Section: Introductionmentioning
confidence: 99%
“…A water supply system (WSS) is safe when it is able to carry out its functions even in the face of undesirable events of various kinds [23]. The consumer is the primary entity to which the concept of safety applies [24,25].…”
Section: Introductionmentioning
confidence: 99%